Empirical studies in UK corporate governance and executive remuneration - Gregory-Smith, Ian (2009)
This thesis is structured around four empirical chapters examining related issues in corporate governance. The sample of FTSE 350 companies 1995-2005 has unique properties which are exploited to advance our understanding of the executive pay-setting process; the turnover of Chief Executives (CEOs); the market's reaction to shareholder activism and voting behaviour; and the distribution of pay within the boardroom.